Numerical Simulation of Fluid-Structure Coupling for a Multi-Blade Vertical-Axis Wind Turbine - Xiao Zhang; Maosheng Zheng (Applied Sciences, 2023)
The aerodynamic characteristics of the vertical-axis wind turbine with three, four, five, and six blades are studied numerically. A coupling model of fluid flow and solid turbine blade is established to model the interactions between air and wind turbine. The pressure distribution and blade deformation affected by air are obtained and discussed. For the four wind turbines with different numbers of blades, the maximum pressure in the entire machine structure occurs at the variable angle position of the blades in the windward region under the same wind speed. Mainly due to the rapid airflow variation, complex turbulence, and significant influence of the wind field on the blades in this position, this part of the blades is prone to bending or damage. Under identical external wind field conditions, wind turbines with four and six blades exhibit significantly higher equivalent pressures on their surfaces compared to those with five and three blades. The maximum equivalent pressure of six blades can reach 3.161 × <semantics>106</semantics> Pa. The maximum deformation of the blade basically occurs at the tip and four sides of the blade. The six-blade wind turbines withstand higher and non-uniform surface pressures on their blades, resulting in the largest deformation of up to 11.658 mm. On the other hand, the four-blade wind turbine exhibits the smallest deformation. The above conclusions provide theoretical guidance for the design and optimization of vertical-axis wind turbines.